Discoidin Domain Receptor-1 (DDR1) is Involved in Angiolymphatic Invasion in Oral Cancer - Yu-Lian Chen (Cancers, 2020)
The discoidin domain receptor-1 (DDR1) is a non-integrin collagen receptor recently implicated in the collective cell migration of other cancer types. Previously, we identified an elevated expression of DDR1 in oral squamous cell carcinoma (OSCC) cells. Through the data mining of a microarray dataset composed of matched tumor-normal tissues from forty OSCC patients, we distilled overexpressed genes statistically associated with angiolymphatic invasion, including DDR1, COL4A5, COL4A6 and PDPN. Dual immunohistochemical staining further confirmed the spatial locations of DDR1 and PDPN in OSCC tissues indicative of collective cancer cell invasion. An elevated DDR1 expression at both the transcription and protein level was observed by treating keratinocytes with collagen of fibrillar or basement membrane types. In addition, inhibition of DDR1 kinase activity in OSCC TW2.6 cells disrupted cell cohesiveness in a 2D culture, reduced spheroid invasion in a collagen gel matrix, and suppressed angiolymphatic invasion in xenograft tissues. Taken together, these results suggest that collagen deposition in the affected tissues followed by DDR1 overexpression could be central to OSCC tumor growth and angiolymphatic invasion. Thus, DDR1 inhibitors are potential therapeutic compounds in restraining oral cancer, which has not been previously explored.